Knowledge, Interest, and Requirements for Participation in a Birth Repository: A Qualitative Study [6E]. (May 2016) - Demment, Margaret; Bullock, Sherita; Nkiruka, Ngozi; Deutsch, Lauren; Dye, Timothy
Abstract : INTRODUCTION: Biorepositories are infrequently developed with community preferences prioritized. This project aims to do this through engaging pregnant women and their broader communities in providing information about their knowledge of, interest in, and requirements for participation in a new placental/birth biorepository being developed. METHODS: Rapid Qualitative Inquiry was implemented through focus groups to better understand attitudes toward development of a birth biorepository. The team debriefed after each focus group to iteratively build upon learnings and to triangulate with subsequent groups. Four focus groups were conducted: two low-income (n=16); one higher income (n=6); and one community (n=9) in partnership with a large community agency and with a large teaching hospital. RESULTS: Few participants had previous knowledge of biorepositories. Participants expressed considerable interest in the potential benefits of a biorepository, though tempered by many concerns that often differed by income. For example, higher-income women were primarily concerned with the ethical implications of research, while lower-income women were concerned with how researchers approached and interacted with them. Women were open to donation of specimens for a biorepository but few supported broad consent. Most women wanted to be informed about current/future research projects and about findings that used their material. CONCLUSION: To effectively recruit a diverse population of peripartum women to participate in a biorepository, efforts are needed to inform and engage potential participants early in the process. New methods respectful of community priorities concerning recruitment, consent, and follow-up are needed to satisfy concerns about participation and to strengthen trust between researchers and communities.